Genome-Wide Single-Nucleotide Polymorphisms in CMS and Restorer Lines Discovered by Genotyping Using Sequencing and Association with Marker-Combining Ability for 12 Yield-Related Traits in Oryza sativa L. subsp. Japonica - Zaid, Imdad U.; Tang, Weijie; Liu, Erbao; Khan, Sana U.; Wang, Hui; Mawuli, Edzesi W.; Hong, Delin (Frontiers in Plant Science, 2017)
Heterosis or hybrid vigor is closely related with general combing ability (GCA) of parents and special combining ability (SCA) of combinations. The evaluation of GCA and SCA facilitate selection of parents and combinations in heterosis breeding. In order to improve combining ability (CA) by molecular marker assist selection, it is necessary to identify marker loci associated with the CA. To identify the single nucleotide polymorphisms (SNP) loci associated with CA in the parental genomes of japonica rice, genome-wide discovered SNP loci were tested for association with the CA of 18 parents for 12 yield-related traits. In this study, 81 hybrids were created and evaluated to calculate the CA of 18 parents. The parents were sequenced by genotyping by sequencing (GBS) method for identification of genome-wide SNPs. The analysis of genotyping by sequencing indicated that the successful mapping of 9.86×106 short reads in the Nipponbare reference genome consists of 39,001 SNPs in parental genomes at 11,085 chromosomal positions. The discovered SNPs were non-randomly distributed within and among the 12 chromosomes of rice. Overall, 20.4% (8026) of the discovered SNPs were coding types, and 8.6% (3344) and 9.9% (3951) of the SNPs revealed synonymous and non-synonymous changes, which provide valuable knowledge about the underlying performance of the parents. Furthermore, the associations between SNPs and CA indicated that 362 SNP loci were significantly related to the CA of 12 parental traits. The identified SNP loci of CA in our study were distributed genome wide and caused a positive or negative effect on the CA of traits. For the yield-related traits, such as grain thickness, days to heading, panicle length, grain length and 1000-grain weight, a maximum number of positive SNP loci of CA were found in CMS A171 and in the restorers LC64 and LR27. On an individual basis, some of associated loci that resided on chromosomes 2, 5, 7, 9, and 11 recorded maximum positive values for the CA of traits. From our results, we suggest that heterosis in japonica rice would be improved by pyramiding the favorable SNP loci of CA and eliminating the unfavorable loci from parental genomes.